Hubungan Antara Big-Five Personality dan Naturalistc Intelligence dengan Enviromental Sensitivity Siswa - Gayu Indri Sulistioningrum (IJEEM - Indonesian Journal of Environmental Education and Management, 2019)
Abstract This research aims to know the relationship between personality and naturalistic intelligence with student's environmental sensitivity. So the problem can be formulated in this study is "is there a relationship between personality and naturalist intelligence with student's environmental sensitivity?". The research was carried out in SMA Negeri 12 Jakarta in October-December 2018 by involving as many as 91 samples of students. The method used is descriptive method with a correlational study approach using simple and multiple correlation regression analysis. The results of the study revealed that there was a positive and significant relationship between the personality of students with environmental sensitivity; student's naturalistic intelligence did not contribute significantly to environmental sensitivity; dan there was relationship not significant between personality and naturalist intelligence of students together with environmental sensitivity. Environmental sensitivity variations on students SMA Negeri 12 Jakarta amounting to 30.3% are determined by the personality but not naturalistic intelligence. Therefore, in increasing the environmental sensitivity of students to be more positive, need to consider factors such as personality of students. Keywords: personality, naturalistic intelligence, environmental sensitivity